2023
DOI: 10.1109/oajpe.2023.3258254
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Electrical Vehicle Private Charging Stations on the Quality of the Low Voltage Network Supply

Abstract: The appearance of new single-phase intensive and often coincident loads, such as the electric vehicle private charging stations (i.e., residential or private parking lots of shopping malls or workplaces), can affect the operation of low voltage (LV) distribution networks. Unbalances among the three-phase loading are extremely common, even if the end-users of a given LV network have similar behaviors. Due to the coincidence of such loads, excessive voltage drops may often appear, altering the quality of supply … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…The implementation of more EV battery charging stations in certain regions may need the installation of new power transformers to adequately meet the demand for EV battery charging. Failure to address this requirement might lead to overheating problems, which in turn can diminish the lifespan of the transformers (Pisano et al, 2023;Chidambaram et al, 2023).…”
Section: Power Quality In Electrical Mobilitymentioning
confidence: 99%
“…The implementation of more EV battery charging stations in certain regions may need the installation of new power transformers to adequately meet the demand for EV battery charging. Failure to address this requirement might lead to overheating problems, which in turn can diminish the lifespan of the transformers (Pisano et al, 2023;Chidambaram et al, 2023).…”
Section: Power Quality In Electrical Mobilitymentioning
confidence: 99%
“…Recent research has reported the impact of electric vehicle charging in the grid [22,68,69], and, thus, power quality-improved electric chargers are designed in [70][71][72]. Isolated solarbased, bidirectional Electric Vehicle Chargers [73] and an off-board PV-Grid Adjustable Charger [74] with Power Quality Enhancement Features are reported in the literature [75].…”
Section: (Viii) Harmonic Elimination Solutionsmentioning
confidence: 99%
“…However, the charging load generated by EVs may have an impact on the stable operation of the distribution network [3,4]. In addition, since each electric vehicle charging station in city gather the charging load of a large number of EVs, the distribution network nodes that supply power to these charging stations will experience more obvious power quality degradation.…”
Section: Introductionmentioning
confidence: 99%